Tracking Neuronal Migration in Adult Brain Slices. Issue 1 (1st April 2015) - Bakhshetyan, Karen; Saghatelyan, Armen
Abstract: Neuronal migration is one of the fundamental processes underlying the proper assembly and function of neural circuitry. The majority of neuronal precursors are generated far away from their sites of integration and need to migrate substantial distances to reach their final destination. Neuronal migration occurs not only in the embryonic brain but also in a few regions of the adult brain such as the olfactory bulb (OB). The mechanisms orchestrating cell migration in the adult brain are, however, poorly understood, despite their clinical relevance. Here we describe a method for time‐lapse imaging of cell migration in acute brain slices. This method, combined with genetic and/or pharmacological manipulations of different molecular pathways, makes it possible to determine the dynamics and molecular mechanisms of cell migration in the adult brain. In addition, time‐lapse imaging in acute brain slices makes it possible to monitor cell movement in a microenvironment that closely resembles in vivo conditions and to study neuroblast displacement along with other cellular elements such as astrocytes and blood vessels. © 2015 by John Wiley & Sons, Inc.